ANALYSIS OF THE ACUTE IMMUNE RESPONSE OF PACIFIC WHITE SHRIMP (Litopenaeus vannamei) INFECTED BY Vibrio parahaemolyticus AND ITS METABOLITES - Rahayu, Indar Widiastuti; Rizkiantino, Rifky; Halalludin, Beni; Herman, Roffi Grandiosa; Dewanti, Lantun Paradhita; -, Iskandar; Wisoyo, Daniel; Sari, Putri Purnama; Rahayu, Mufti; Fitriana, Rachmawati Nur; Panjaitan, Bestran Virlando; Haliman, Rubiyanto Widodo; Laiman, Hendri (Jurnal Kedokteran Hewan, 2024)
This study was aimed to observe the survival rate (SR) and clinical signs, and the acute immune response of Pacific white shrimp (Litopenaeus vannamei), including total hemocyte count (THC), bacterial clearance, and prophenoloxidase (ProPO) activity due to infection with the Vibrio parahaemolyticus bacteria and its metabolites. Shrimp were infected by bacterial isolates with culture media (A), bacterial isolates without culture media (B), and metabolites suspensions from bacterial culture media (C) for 8 hours with observation every 2 hours. The results showed that experimental shrimps in groups A and B showed clinical signs and reduced SR, 24.44% and 62.22%, respectively. Experimental group C still showed the clinical signs but did not cause the mortality (SR 100.00%). The THC did not show significant changes, either based on experimental groups or duration of infection, but all groups tended to show decreasing THC at 8 hours post-infection. Bacterial clearance and ProPO activity also did not show significant differences between experimental groups or duration of infection at 8 hours post-infection. However, there was an increase in bacterial clearance activity at 6 hours post-infection in the experimental groups A and B. Based on the study results, the acute immune response in shrimp from all of the experimental groups did not show significant changes at 8 hours post-infection. However, group A significantly decreased SR compared to groups B and C.